Implementasi Perangkat Mobile Publisher Subscriber Sebagai Perantara Pengiriman Data Sensor Dari Lapangan Ke Pusat Data - Sukma Alamsyah Budianto; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sensor devices implemented in the field facing a problem when sending data on unstable network conditions to the data center. To solve these problems, we develop an application based on the Android operating system implementing publish/ subscribe communication as an intermediary for sending sensor data in the field to the data center using the MQTT protocol. To prove the application can operate as an intermediary for sending sensor data in the field to the data center, three tests are carried out. There are functional testing, scenario testing and performance testing. In functional tests, five functional requirements designed can be fulfilled by the application as an intermediary for sending sensor data to the data center. In scenario tests, from the three test scenarios performed the results of the application can be carried out without any application errors. In performance testing by calculation application performances and get the results of Subscriber Throughput is equal to 161.55 message/s, Publihser Throughput is equal to 2.13 message/s, the latency message average Subscriber apps are 1488.28 ms and the publisher message latency average app is 5208.86 ms.